Russian Kurdоlоgist Оlga Ivаnоvnа Zhigаlinа 1946-2013 - Hawraz Jawhar Majid; Nahro Ismael Muhammad (Zanco Journal of Humanity Sciences)
Zhigalina is regarded as one of the most famous Russian Kurdologist all over Russia who has conducted a large number of scientific researches about Kurdish history. She has worked with many well-known orientalists like Lazarif, PrImakof and Khalfin. They assisted her to become Kurdologist as well as focusing on the problems and the history of Kurdish nation. She has published most of her writings and papers in Russian language and published them in Moscow Institute of Oriental Studies journal. Moreover, she has published some of her writings in Russian and German languages in the European Journals. She has had an effective and important role in introducing the history of Kurdish and nation and their problems to the European countries. In 2004, she became the director of the Kurdish Cabinet at Institute of Oriental Studies of the Russian Academy of Science until she passed away at her workplace on 23rd October 2013.